Translation and psychometric validation of the Patient Participation Culture Tool for healthcare workers in Chinese nursing context - Wenna Wang; Shanshan Wang; Qianqian Sun; Zhenxiang Zhang; Chenxi Zhou; Qiushi Zhang; Yongxia Mei (BMC, 2024)
Abstract Background Promoting patient participation stands as a global priority in nursing care. Currently, there is a lack of a standardized tool to assess the culture of patient participation from the perspective of nurses in China. Aims To translate and examine the validity and reliability of the Patient Participation Culture Tool for healthcare workers (PaCT-HCW) on general hospital wards in Chinese nursing context. Methods A cross-sectional research study was conducted among 812 nurses. Brislin's recommendations were adhered to during the translation of the scale. Validity was assessed using construct validity, content validity, and face validity. Split-half reliability, test-retest reliability, and internal consistency reliability were used to evaluate dependability. The study was guided and reported following the STROBE checklist and recommendations for reporting the results of studies of instrument and scale development and testing. Results The Chinese version of PaCT-HCW (the PaCT-HCW-C) exhibits good face validity and content validity. A rigorous exploratory factor analyse verified a six-factor (competence, support, perceived lack of time, information sharing and dialogue, response to questions and acceptance of a new role) scale structure with a cumulative variance contribution of the factors with 44 items of 68.840%. With a Cronbach's α coefficient of 0.962, split-half reliability of 0.866, and intraclass correlation coefficients of 0.989, the instrument demonstrates great reliability. Confirmatory factor analysis results validated the consistency of the six factors with the structure of the PaCT-HCW-C scale. Conclusions The 44-item PaCT-HCW-C is a valid and reliable instrument with satisfactory psychometric properties. It could serve as a tool for assessing the effectiveness of international programs aimed at fostering patient participation from the perspective of nurses, while also providing insights from China's practical experiences.